1998
DOI: 10.1021/ja9804114
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Activation of CO2 on RhI(CO)2/Al2O3−CO2 Dissociation and Oxygen Atom Exchange

Abstract: The ultraviolet (3.8 eV) photolysis of atomically dispersed RhI(13C18O)2 species supported on an Al2O3 surface in the presence of CO2 at 256 K has been studied by infrared spectroscopy (FTIR). Carbon dioxide is activated on photochemically produced RhI(13C18O) sites to produce various isotopically labeled rhodium gem-dicarbonyl species. The two major products of CO2 activation exhibit infrared bands at 2077 and 1958 cm-1 assigned to RhI(12C16O)(13C18O) species and bands at 2036 cm-1 and near 1958 cm-1 assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Clearly, bands in the 2200-2165 cm -1 region are enhanced by CCl 4 , products in the 2040-2010 cm -1 region are little affected, but bands in the 1920-1800 cm -1 region are markedly decreased. Experiments were also done with 13 CO, C 18 O, and a mixture of 12 CO and 13 CO, and the product absorptions are listed in Table 1. Calculations were performed on the monocarbonyl and dicarbonyl neutrals, cations and anions, and the isotopic carbonyl frequencies are listed in Tables 2 and 3 for comparison with experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, bands in the 2200-2165 cm -1 region are enhanced by CCl 4 , products in the 2040-2010 cm -1 region are little affected, but bands in the 1920-1800 cm -1 region are markedly decreased. Experiments were also done with 13 CO, C 18 O, and a mixture of 12 CO and 13 CO, and the product absorptions are listed in Table 1. Calculations were performed on the monocarbonyl and dicarbonyl neutrals, cations and anions, and the isotopic carbonyl frequencies are listed in Tables 2 and 3 for comparison with experiment.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] This gem-rhodium dicarbonyl species is usually designated Rh I (CO) 2 because of agreement with the C-O stretching modes of the (OC) 2 Rh(Cl) 2 Rh(CO) 2 molecule, where the oxidation state of rhodium is +1. 6,7,9 The rhodium dicarbonyl on alumina, silica, and zeolites is widely used as a catalyst system for activation of many molecules including H 2 , N 2 , CO 2 , and alkanes [10][11][12][13][14][15] through a coordinatively unsaturated Rh I (CO) center, which absorbs near 2096 cm -1 on zeolites, 16 2070 cm -1 on silica, 17 and 2060 cm -1 on alumina. 4,11 Furthermore, the activation of C-H bonds in alkanes by a transient CpRh(CO) species absorbing near 1985 cm -1 in the gas phase readily occurs.…”
Section: Introductionmentioning
confidence: 99%
“…66 As an example, a study by Wovchko and Yates demonstrated the activation of CO 2 by a metal complex (Rh I (CO) 2 ) immobilized on an alumina support. 57 Similar studies should lead to the rational design of photocatalysts mediating CO 2 reduction. The surface chemistry of CO 2 on metals and oxide surfaces was reviewed by Freund and Roberts.…”
Section: Thermodynamics and Initial Steps Of Co 2 Activation And Furt...mentioning
confidence: 94%
“…Some recent developments in this field have been moved towards rational photocatalyst design, the use of highly active isolated Tispecies in mesoporous and microporous materials, 11,14,15,[36][37][38]55,56 metal-doping of TiO 2 , development of catalysts active at longer wavelengths than can be achieved with commercially available titania, and the elucidation of reaction mechanisms through in situ spectroscopic studies. 14,57 A comparison of the CO 2 conversion rates from various studies is shown in Fig. 3.…”
Section: Current State Of Co 2 Photoreduction On Tio 2 -Based Catalystsmentioning
confidence: 99%
“…[ 27 ] In the 1990s to 2000s, more studies established that a single‐metal atom is capable of driving catalytic reactions (e.g., Pt SAs on MgO). [ 28–31 ] Flytzani‐Stephanopoulos’ group in 2003 studied single‐site Au and Pt catalysts, showing that they exhibited high performance, despite after removing the corresponding nanoparticles, suggesting the residual Au/Pt species were the active sites toward water–gas shift reaction. [ 32 ] Pd SAs and Ir SAs on Al 2 O 3 and MgO supports were directly observed by Lee and co‐workers and Gates and co‐workers.…”
Section: Introductionmentioning
confidence: 99%